Use of SAS Studio Software in the analySiS and visualisation of spatial data on historical changes in land use and land cover in South-East Poland in the twentieth century - Dorocki, Sławomir (Studia Historiae Oeconomicae, 2025)
The use of statistical tools is becoming increasingly useful for the analysis of spatial numerical data. The following article attempts to create a model of changes in land use and land cover in the years 1900 and 1990 using SAS Studio software. The created model referred to the area of historical West and Central Galicia (part of East Galicia). This is the area of the former Austrian partition, and it is currently located within the borders of Poland. The evolution of the share of agricultural and forest areas in the system of statistical localities in the analysed years was subjected to analysis. The index of change in land use and land cover structure was calculated based on share differences. The biggest changes in land cover were recorded in the eastern part of the region under study and in areas where political borders were modified. A model of change in the structure of land use and land cover was created based on selected indices of the level of economic development at the beginning of the twentieth century. A comparison of the model created with the values observed on the basis of statistical data revealed that the greatest disturbance of the model took place in the eastern part of the region under study. This was mainly due to the political and demographic changes that took place in the twentieth century.